Avaliação da educação superior: o sistema de bibliotecas da UFPB e a evolução dos seus indicadores de desempenho - Costa, João Henrique Lucena da (2017)
The present research aims to analyze the performance of the Library System of the UFPB in the institutional and course evaluation in the context of the management and evaluation policy, through the evaluation parameters of the MEC, from the creation of the National System of Evaluation of Higher Education (SINAES). Assuming the advent of the REUNI, several conditions and possibilities arose, especially in the expansion of resources and investments for federal universities, reflecting directly on the Libraries, which are departments associated to university systems. The initial hypothesis pointed to the acquisition of books and materials, which positively impacted and could provide an improvement or not of the performance of the Library System. The theoretical foundation is based on the concept of Management State and studies related to the Reform of the Brazilian state and public policies in higher education (university/society, and higher education) and the study of the university library (public policies for university libraries, Evaluation of libraries). Regarding the methodology, the way forward was the adoption of exploratory and descriptive research, with a mixed - quantitative and qualitative approach from the point of view of the approach to the problem. The data were collected in a bibliographical, direct and indirect documentary and the method of approach was the hermeneutic. According to the results, the Library System as a whole obtained a sufficient/regular concept; however, some of these indicators obtained insufficient/weak concepts. The research showed the existence of strengths, such as online access to CAPES Periodical Portals, in addition to the broad and permanent hours of operation of libraries. Among the fragile points found, mentioned the inexistence or insufficient number of titles and their respectives copies of the basic and complementary bibliography in libraries. In the final considerations, and as a suggestion to improve attendace, services provision and products offering, it is proposed the elaboration of an Improvement Management Plan, in accordance with SINAES, aiming at the advancement and the development of the indicators of the Library, in addition to the implementation of a more effective policy for the Library System, concerning to the acquisition of bibliographies.